2013
DOI: 10.1071/cp12401
|View full text |Cite
|
Sign up to set email alerts
|

Dry matter and nitrogen partitioning and translocation in winter oilseed rape (Brassica napus L.) grown under rainfed Mediterranean conditions

Abstract: For crops grown in Mediterranean environments, translocation of pre-anthesis assimilates to the fruit is of great importance, because hot and dry conditions during fruit ripening diminish net assimilation rate and nitrogen (N) uptake. This field study was conducted to assess the pattern of dry matter and N accumulation and the role of assimilate translocation in pod development of oilseed rape plants in a Mediterranean environment. Four cultivars of winter oilseed rape (Brassica napus L.), i.e. three hybrids (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 33 publications
4
3
0
Order By: Relevance
“…Across the two seasons, NHI decreased with increased post-flowering N uptake (r = −0.75; P = 0.0006; n = 11). Nitrogen harvest index values reported here are within the range reported for canola by Papantoniou et al (2013) [0.25-0.47 in the present study vs 0.32-0.66 reported by Papantoniou et al (2013)] and close to the lower range reported by Ma and Herath (2016) (0.41-0.83) but much lower than the findings of Hocking and Stapper (2001a).…”
Section: Discussionsupporting
confidence: 89%
“…Across the two seasons, NHI decreased with increased post-flowering N uptake (r = −0.75; P = 0.0006; n = 11). Nitrogen harvest index values reported here are within the range reported for canola by Papantoniou et al (2013) [0.25-0.47 in the present study vs 0.32-0.66 reported by Papantoniou et al (2013)] and close to the lower range reported by Ma and Herath (2016) (0.41-0.83) but much lower than the findings of Hocking and Stapper (2001a).…”
Section: Discussionsupporting
confidence: 89%
“…Although paclobutrazol reduced the relative growth rate for stems and the rate of biomass allocation to stems, it significantly increased both the parameters with respect to roots. Earlier work has shown that reduced biomass allocation to stems results in higher yields (Papantoniou et al 2013). In the present study, reducing the allocation to stems increased the allocation to roots -thereby forming a strong root system -and also increased the translocation of stored substances in stems to roots and pods.…”
Section: Discussionsupporting
confidence: 62%
“…However, in typically Mediterranean climate, seasons may be either mild and wet or extremely dry. In our study, in 2008, seed filling fell during a period characterized by high temperatures and drought, affecting yield components, and as consequence seed production, as already stated by other authors [4,56] in their studies in Mediterranean-type climate.…”
Section: Methodssupporting
confidence: 64%